Features of active medium for wide-band spectrum tuned dye laser - Maslov, V.V. (Functional Materials, 2014)
Spectral, fluorescent and lasing characteristics of mixtures of three couples of the laser dyes have been studied with the purpose of broadening the laser tunable range. We have used the dyes those have the absorption spectra in the close spectral regions near wavelength of pumping, but their fluorescence spectra have essentially different Stokes shift. As a result, the fluorescent band of these dye mixtures expands. It is noted the substantial condition for these mixtures of the dyes is the absence of nonradiating losses which may be appeared under interaction of the dye molecules or under interaction of them with the solvent molecules. The continuous tuning of laser radiation more than 100 nm: through-out the yellow and red ranges from 572 nm to 687 nm has been fulfilled under laser pumping with only one solution of Rh6G and DCM mixture in DMSO.